PTH-095 The Northern Ireland Experience of Selective Internal Radiation Therapy. (17th August 2016) - Layard, BV; McNeice, A; Kennedy, PT; Cash, WJ; McDougall, NI
Abstract : Introduction: Selective Internal Radiation Therapy (SIRT) is liver-directed therapy for the treatment of non-resectable primary or secondary liver tumours. Radioactive microspheres containing yttrium-90 are delivered into the arterial blood supply of the liver, where they become lodged in vessels within the tumour, allowing targeted radiation therapy to occur. Currently this innovative treatment concept is recommended when established treatment regimens have failed. Methods: SIRT is performed at a single regional centre in Northern Ireland. All potential candidates are discussed at a regional hepatobiliary multi-disciplinary meeting and all have appropriate work-up for SIRT performed to exclude shunting. Each patient receives sensitising chemotherapy in the days prior to SIRT unless contraindicated. We reviewed all SIRT treatments, looking at indications, complications and outcomes between September 2010 and September 2015. Results: 27 patients underwent SIRT. The mean age was 62 years old (range 41–77). The indications were liver metastases secondary to colorectal cancer (63%), hepatocellular carcinoma (30%), and liver metastases secondary to neuroendocrine tumours (7%). Each patient had a follow up single-photon emission computed tomography (SPECT) scan within 24 hours, none of which demonstrated any significant extra-hepatic activity. 6 patients remain alive at the time of writing with a time range of between 6 and 28.6 months post-SIRT. Of the remaining 21 patients, the median survival was 9.2 months (ranging from 25 days to 59.4 months). Complications Two patients died within 30 days. One, aged 72, with liver metastases from colorectal cancer died from progression of liver metastases with jaundice and ascites. The other, aged 77, with hepatocellular carcinoma died from multi-organ failure. One patient, treated for hepatocellular carcinoma with underlying Childs-Pugh B cirrhosis died 39 days following SIRT with decompensation of his liver disease. Conclusion: Survival in the 3 patient groups treated by SIRT at our centre showed wide variation. In particular, those receiving SIRT for HCC following prior TACE therapy had the poorest survival. The optimal indications for SIRT have yet to be clarified but our initial experience suggests that using SIRT in HCC patients after TACE therapy has been exhausted may not be the best approach. Disclosure of Interest: None Declared